2022
DOI: 10.1126/sciadv.abo6254
|View full text |Cite
|
Sign up to set email alerts
|

Psychological inoculation improves resilience against misinformation on social media

Abstract: Online misinformation continues to have adverse consequences for society. Inoculation theory has been put forward as a way to reduce susceptibility to misinformation by informing people about how they might be misinformed, but its scalability has been elusive both at a theoretical level and a practical level. We developed five short videos that inoculate people against manipulation techniques commonly used in misinformation: emotionally manipulative language, incoherence, false dichotomies, scapegoating, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
181
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 54 publications
2
181
0
3
Order By: Relevance
“…People's attitudes towards topics in science hinge on factors most scientists do not view as objectively relevant to how we should understand the evidential quality of a piece of scientific research. For example, it has been established that perceptions of scientific consensus shape how people evaluate a piece of science (Cook & Lewandowsky, 2016;Imundo & Rapp, 2022;Roozenbeek, van der Linden, Goldberg, Rathje, & Lewandowsky, 2022;Van der Linden et al, 2019). "Gateway beliefs" to climate attitudes and perceptions of consensus play a pivotal role in shaping how evidence for climate change is integrated into people's belief systems.…”
Section: Implications For Intervention Developmentmentioning
confidence: 99%
“…People's attitudes towards topics in science hinge on factors most scientists do not view as objectively relevant to how we should understand the evidential quality of a piece of scientific research. For example, it has been established that perceptions of scientific consensus shape how people evaluate a piece of science (Cook & Lewandowsky, 2016;Imundo & Rapp, 2022;Roozenbeek, van der Linden, Goldberg, Rathje, & Lewandowsky, 2022;Van der Linden et al, 2019). "Gateway beliefs" to climate attitudes and perceptions of consensus play a pivotal role in shaping how evidence for climate change is integrated into people's belief systems.…”
Section: Implications For Intervention Developmentmentioning
confidence: 99%
“…There are only a few studies of this kind that demonstrated measurable effects in media truth discernment after one month. Among these attempts, only a few met the important criteria of scalability (Guess et al, 2020;Roozenbeek et al, 2022). We based our intervention on this work and aimed to modify it in a way that might strengthen the long-term effects in digitally vulnerable groups, such as pro-Orbán conservatives.…”
Section: Study 2 a Prosocial Intervention To Motivate Eastern Europea...mentioning
confidence: 99%
“…Inoculation 7,8,9,10,11,12,13,14,15,16,17,18,19,20 and other forms of digital media literacy interventions 8,14,15,17,20,21,22,23,24,25 similarly struggle to produce reliable long-term effects.…”
Section: Fake-news Interventions Scalability and Long-term Effectsmentioning
confidence: 99%
“…The question therefore is: what could sustain the desired change in news consumption behaviors? We suggest that prosocial motivations can contribute more (e.g., 29,30 ) than those, predominantly individual intellect-related drivers (e.g., 16 ), that the above approaches try to leverage. We root our psychological intervention in the richly understood prosocial motives of our post-socialist Hungarian sample.…”
mentioning
confidence: 91%
See 1 more Smart Citation